2010
DOI: 10.1101/gad.1932810
|View full text |Cite
|
Sign up to set email alerts
|

s-SHIP promoter expression marks activated stem cells in developing mouse mammary tissue

Abstract: Mammary stem cells (MaSCs) play critical roles in normal development and perhaps tumorigenesis of the mammary gland. Using combined cell markers, adult MaSCs have been enriched in a basal cell population, but the exact identity of MaSCs remains unknown. We used the s-SHIP promoter to tag presumptive stem cells with GFP in the embryos of a transgenic mouse model. Here we show, in postnatal mammary gland development, that GFP [Keywords: Stem cell; mammary gland development; cap cells; alveolar bud cells; s-SHIP;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
119
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 52 publications
(72 reference statements)
6
119
0
Order By: Relevance
“…Similar results were also obtained when the Wnt receptor LPR5 was deleted [23]. A recent study showed that using a GFP reporter driven by the s-SHIP promoter, GFP + replicating "active" MaSCs can be identified in cap cells in puberty and basal alveolar bud cells in pregnancy, but not in adult virgin animals, or in mammary tissues during lactation or involution stages [16]. Future characterizations will help to better understand whether or not distinct MaSC populations exist, and how they are controlled by their local micro-environmental cues.…”
Section: Identification Of Mascssupporting
confidence: 65%
See 2 more Smart Citations
“…Similar results were also obtained when the Wnt receptor LPR5 was deleted [23]. A recent study showed that using a GFP reporter driven by the s-SHIP promoter, GFP + replicating "active" MaSCs can be identified in cap cells in puberty and basal alveolar bud cells in pregnancy, but not in adult virgin animals, or in mammary tissues during lactation or involution stages [16]. Future characterizations will help to better understand whether or not distinct MaSC populations exist, and how they are controlled by their local micro-environmental cues.…”
Section: Identification Of Mascssupporting
confidence: 65%
“…The peak of this expansion seems to occur mid-to late-pregnancy at the end of alveolar proliferation and the onset of differentiation to begin milk production. Although s-SHIP promoter-driven GFP reporter marks active MaSCs in both the puberty and pregnancy stages [16], it is unknown whether pregnancyassociated MaSCs come from the same stem cell population important for pubertal growth, or if a distinct MaSC population exists or is responsible specifically for growth during pregnancy. While the start of milk production corresponds with the drop in MaSC numbers, sustained milk production continues to affect the rate of MaSC apoptosis, as when mothers do not nurse their young MaSC numbers drop quicker than those who do nurse their young [22].…”
Section: Mammary Epithelial Cell Dynamics During Development and Pregmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that with the use of a GFP reporter driven by the s-SHIP promoter, GFP+ replicating active MaSCs can be identified in cap cells at puberty and basal alveolar bud cells in pregnancy, but not in adult virgin animals, or in mammary tissues during lactation or involution stages [89].…”
Section: Mammary Gland Stem Cells (Mascs)mentioning
confidence: 99%
“…The predominance of immature epithelial cells in embryo provides the target for the initiation of tumorigenesis when intrauterine hormone concentration is high. Indeed, animal studies showed that undifferentiated TEB is the most susceptible to carcinogen for the formation of tumor (Bai and Rohrschneider, 2010;Roussos et al, 2010;Russo and Russo, 1994). Recent evidence even points to the immature gland in utero as the target for the initiation of breast cancer (Brisken and O'Malley, 2010;Hardy et al, 2010;Hilakivi-Clarke and Clarke, 1998;Sanderson et al, 1998;Torres-Arzayus et al, 2010).…”
mentioning
confidence: 99%